Spontaneous Respiration Intubation as a Cornerstone of Multidisciplinary Management for Delayed Tracheoesophageal Fistula Repair in a Critically Ill Neonate - Sulthoni; Dino Irawan; Novita Anggraeni; Nopian Hidayat; T Addi Saputra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: The perioperative management of neonates with esophageal atresia and Type C tracheoesophageal fistula (EA/TEF) is exceptionally challenging, particularly in cases of delayed diagnosis complicated by aspiration pneumonia and congenital heart disease. The primary anesthetic risk is catastrophic gastric insufflation and hemodynamic collapse from positive pressure ventilation (PPV) before fistula control. This report details a successful multidisciplinary strategy centered on an airway technique that preserves spontaneous ventilation. Case presentation: A 16-day-old, 2.5 kg female neonate with Type C EA/TEF presented for surgical repair following a delayed referral. The case was critically complicated by severe aspiration pneumonia (cultures positive for Klebsiella pneumoniae), which was managed with targeted antibiotic therapy, and hemodynamically significant congenital heart defects (2.5 mm patent ductus arteriosus, 3 mm patent foramen ovale). After 48 hours of intensive cardiorespiratory and nutritional optimization in the neonatal intensive care unit (NICU), the patient underwent surgery. To circumvent the life-threatening risks of PPV, an inhalational induction with sevoflurane was performed, maintaining spontaneous ventilation. The airway was secured via direct laryngoscopy without neuromuscular blockade. A right extrapleural thoracotomy, fistula ligation, and primary esophageal anastomosis were successfully performed. Intraoperative lung retraction-induced desaturation was managed with coordinated surgeon-anesthetist maneuvers. The postoperative course was uneventful. Conclusion: In a high-risk neonate with delayed TEF presentation and profound cardiorespiratory compromise, securing the airway while maintaining spontaneous ventilation is a cornerstone of safe anesthetic practice. This approach, integrated within a comprehensive, multidisciplinary management plan, directly mitigates the risk of gastric perforation and cardiovascular collapse, thereby enabling a successful surgical repair and favorable outcome.